F (x) = Sin x
F’ (x) = Cos x
F (x) = Cos x
F’ (x) = -Sin x
F (x) = Tan x
F’ (x) = Sec² x
F (x) = Cot x
F’ (x) = -Csc² x
F (x) = Sec x
F’ (x) = Sec x ⋅ Tan x
F (x) = Csc x
F’ (x) = -Csc x ⋅ Cot x
F (x) = bx
F’ (x) = bx ⋅ ln b
F (x) = ex
F’ (x) = ex
#^x
#^x * ln#
F (x) = logb x
F’ (x) = 1/(x ⋅ ln b)
F (x) = ln x
F’ (x) = 1/x
Add/Sub Rule - [f(x)+g(x)] d/dx
f’(x) + g’(x)
Product Rule - [f(x)*g(x)] d/dx
[f’(x) * g(x)] + [g’(x) * f’(x)]
Quotient Rule - [f(x)/g(x)] d/dx
f(x)=hi
d(x)=lo
g(x )* f’(x) - f(x) * g’(x) / g(x)²
lodihi minus hidilo over lolo
Power Rule - [x^n] d/dx
n * x^(n-1)
Coeffiecient Rule - [k*f(x)] d/dx
k * f’(x)
Constant Rule - [k] d/dx
0
arc
inverse of trig identity
d/dx [sin-1(x)]
d/dx [cos-1(x)]
d/dx [tan-1(x)]
d/dx [sec-1(x)]
d/dx [csc-1(x)]
d/dx [cot-1(x)]